(untitled) (Research, Society and Development, 2021)
Technology is a tool that has been facilitating the daily life of society in various sectors, specifically in the area of ​​education, but it is extremely important to be prepared. The general objective of this work is to demonstrate the challenges faced by teachers during the period of remote teaching, which was established due to the Covid-19 pandemic. Consequently, the study will contextualize alternatives to facilitate teacher performance during classes and maximize educational and professional outcomes. Effectively, this study will address the following issue: What are the challenges of teaching in times of pandemic? The methodology used for the development of the current work is the bibliographic review, which will analyze the data in a quantitative and qualitative way, with an emphasis on collections of national and international credibility. What justifies the development of this work is the absence of academic materials dealing with the subject, in addition to the need to demonstrate technology challenges in remote classes, resulting from the pandemic. It is concluded that technology is essential for the development of teachers and students, but it is necessary to have training and qualification for the use of equipment, as the lack of training and qualification causes difficulties in learning and in the pedagogical process in the years initials of Elementary School.